Heart sign in Neurology - A Radiological sign - Sajan, Sheetal; Thomas, Reji (Nepal Journal of Neuroscience, 2020)
Bilateral medial medullary infarction is a rare stroke syndrome. The common symptoms are quadriparesis, dysarthria and hypoglossal palsy. However, the early diagnosis of bilateral medial medullary infarction may be difficult as it may mimic other conditions like Guillain Barre syndrome and brainstem encephalitis. With the advent of magnetic resonance imaging, it can be easily diagnosed, as the diffusion weighted sequences demonstrate hyperintensity involving bilateral medulla in a heart shaped pattern, described as the “Heart sign”. We hereby report a patient who presented with progressive quadriparesis, and dysarthria, progressing to respiratory failure, whose MRI brain showed the characteristic “heart sign” on diffusion sequences and was diagnosed to have bilateral medial medullary infarction.